Long-term functional outcome after moderate-to-severe paediatric traumatic brain injury. (June 2014) - Shaklai, Sharon; Peretz, Relly; Spasser, Raluca; Simantov, Maya; Groswasser, Zeev
Abstract Background: Long-term follow-up studies after severe and moderate pediatric traumatic brain injury (TBI) are not common and inconclusive. Most studies focused on neurobehavioural sequelae, less data is reported about age appropriate function. Different prognostic factors were noted over past decades. Methods: A prospective historical study describing the functional long-term outcome after childhood moderate and severe TBI was conducted. Seventy-seven children who suffered either severe or moderate TBI were followed for an average of ten years and clinical functional outcome was recorded. Factors influencing prognosis were investigated. Results: All children but six were integrated into educational systems after discharge from rehabilitation settings (department and day-care); 61% of children who suffered severe-moderate TBI were able to function within their normative age peers. Positive outcome predictors were Glasgow Coma Scale (GCS) >5, length of unconsciousness (LOC) <11 days, Functional Independence Measure (FIM) and Intelligence Quotient (IQ) at discharge from rehabilitation, length of acute hospitalization and rehabilitation. Negative outcome predictors were vegetative state at admission to rehabilitation and associated anoxic brain injury. Conclusions: Guarded optimistic functional outcome can be expected after severe or moderate childhood TBI.